Analysis of the Influence of Learning Environment, Learning Motivation, Social Support, Student Psychological Well-Being and Academic Performance - Huswatun Hasanah; Karmila; Julia Dwi Mawarni (Institute of Information Technology and Social Science (IITSS), 2022)
This study aims to analyze the influence of learning environment, learning motivation, social support, psychological well-being of students and academic performance at Jambi university. This study uses a quantitative approach and the data collection technique is in the form of distributing questionnaires and collecting questionnaires (surveys) through Google Forms. Respondents selected in this study were Jambi University students with a sample size of 103 people from a total population of 10,000 people. The data analysis technique used in this research is Partial Least Squares-Structural Equation Modeling (PLS-SEM) to develop a model that describes the relationship between variables. The results of this study indicate that in the first hypothesis, social support has a P value of 0.037 which indicates a significant influence on academic performance. In the second hypothesis, learning motivation has a P-value of 0.075 which also shows a significant influence on academic performance. Finally, in the third hypothesis, the learning environment has a P-value of 0.522, which shows a significant influence on academic performance. Therefore, this study concludes that social support, learning motivation, and learning environment have a positive and significant influence on students' academic performance. Therefore, improving students' academic performance can be achieved through increasing social support, motivation, and learning environment. This study uses a quantitative approach and the data collection technique is in the form of distributing questionnaires and collecting questionnaires (surveys) through Google Forms. Respondents selected in this study were Jambi University students with a sample size of 103 people from a total population of 8,968 people. The data analysis technique used in this research is Partial Least Squares-Structural Equation Modeling (PLS-SEM) to develop a model that describes the relationship between variables. The results of this study indicate that in the first hypothesis, social support has a P-value of 0.037 which indicates a significant influence on academic performance. In the second hypothesis, learning motivation has a P-value of 0.075 which also shows a significant influence on academic performance. Finally, in the third hypothesis, the learning environment has a P-value of 0.522, which shows a significant influence on academic performance. Therefore, this study concludes that social support, learning motivation, and learning environment have a positive and significant influence on students' academic performance. Therefore, improving students' academic performance can be achieved through increasing social support, motivation, and learning environment.